Are arrival date and body mass after spring migration influenced by large-scale environmental factors in a migratory seabird? - Szostek, K. Lesley; Bouwhuis, Sandra; Becker, Peter H. (Frontiers in Ecology and Evolution, 2015)
Changes in the timing of migratory events have been observed recently in many migratory species, most likely in response to climatic change. In the common tern Sterna hirundo we examined such changes in spring arrival date and body mass based on a 19 year individual-based longitudinal data from a transponder marked colony from 1994 - 2012. Although no long-term trend was observed in either trait, strong inter-annual and age-specific variation in arrival date and mass was evident. We investigated whether environmental factors such as (i) global climate phenomena North Atlantic and Southern Oscillation Indices NAOI and SOI, or (ii) local factors, such as food abundance in the wintering and breeding area, represented by fish stock or marine primary productivity, could explain this variation. We found that 2-year-old birds on their first spring migration advanced arrival relative to spring NAOI and delayed arrival relative to sprat Sprattus sprattus abundance. The arrival date of 3-year-olds also advanced in relation to NAOI and delayed in relation to winter SOI. In contrast, adults delayed arrival with NAOI and advanced relative to SOI. Within age groups, earlier annual arrival coincided with higher mass, indicating that a fast and/or early migration did not come at a cost to body condition. Changes in arrival mass relative to environmental covariates were found only in 2-year-olds on their first spring migration: in these birds arrival mass was positively related to herring Clupea harengus and sprat abundance in the breeding area as well as spring NAOI and negatively related to SOI. In conclusion, traits related to migration of common terns were linked with environmental conditions, but showed no long-term trends over the past two decades. Age-related differences were marked, suggesting that common terns might be subject to differing environmental constraints or respond differently to conditions during their annual cycle depending on age.